Problematika Pembelajaran Bahasa Arab di Madrasah Ibtidaiyah: Analisis Pedagogis, Linguistik, dan Psikologis Berbasis Studi Fenomenologis di MIN 6 Sukoharjo - Insan, Muslikhah Al Fikriyatul (Jurnal Pendidikan Madrasah, 2026)
This study aims to analyze the problems in Arabic language learning and to formulate strategies for addressing them in class 5A of MIN 6 Sukoharjo. The research employed a qualitative approach with a phenomenological design to gain an in-depth understanding of the experiences of teachers and students. Data were collected through interviews, observations, and documentation involving the principal, teachers, homeroom teacher, and students as informants. The findings reveal that although the learning process has been implemented according to instructional stages, it still faces complex and multidimensional challenges. From the teachers’ perspective, the limited number of teaching staff results in a heavy workload, compounded using conventional and less innovative teaching methods. From the students’ perspective, low learning motivation, diverse initial abilities, and difficulties in understanding and memorizing materials constitute major obstacles. This is reflected in the low academic achievement, with most students not meeting the minimum competency criteria. Other contributing factors include dense and less contextual learning materials, limited instructional time, large class sizes, and insufficient learning facilities. External factors, particularly the low level of parental involvement, further affect the learning process. Efforts to address these issues include enhancing teacher competence, implementing varied and communicative teaching methods, increasing student motivation, simplifying and contextualizing learning materials, and strengthening collaboration between schools and parents.